Influence of sexual maturation on anaerobic performance of male adolescent wrestlers (Revista de Artes Marciales Asiáticas, 2024)
This study aimed to examine the impact of sexual maturation on the anaerobic performance of male adolescent wrestlers. Methods: We included a sample of 29 freestyle and Greco-Roman wrestlers from various clubs in Barinas, Venezuela. Their physical characteristics were as follows (mean ± SD): age, 14.99 ± 1.83 years; body mass, 54.68 ± 16.80 kg; height, 161.06 ± 12.78 cm; body fat, 12.09 ± 4.11%; body mass index (BMI), 20.58 ± 3.79 kg/m2; and training experience, 3.66 ± 2.27 years. Sexual maturation was evaluated using Tanner's criteria, while anaerobic performance was assessed with the 30-second Wingate test for both lower and upper body. Results: There were moderate to strong significant correlations between maturation development and both peak power (PP) and average power (AP) — for both absolute and relative measures — for the lower and upper body. The fatigue index (%FI) for the lower body did not show any correlation with maturation development or with the pubescent and postpubescent maturation categories. Conversely, the %FI for the upper body demonstrated a significant moderate correlation with maturation development and with the postpubescent maturation category. Additionally, a strong significant correlation was observed between the pubescent maturation category and both PP and AP (absolute and relative) for the lower body. A moderate correlation was found between the postpubescent category and PP (absolute) for the upper body. PP (absolute) and AP (relative) for the upper body had a moderate correlation with the pubescent maturation category, while the postpubescent category showed a strong correlation with PP (absolute), AP (absolute), and AP (relative). Conclusion: The stages of sexual maturation significantly influence the anaerobic capacity of adolescent wrestlers, potentially affecting their training adaptations for peak performance. Future research should explore the physiological responses to training protocols tailored to specific stages of maturation.